The Saigo operator applied to some special functions - Matera, Josefina; González, Beatriz (Rev. Téc. Fac. Ing. Univ. Zulia)
The Saigo fractional operators are defined using the Gauss hypergeometric functions as kernel. They generalize Riemann-Liouville, Erdélyi-Kober and Weyl operators. In this article, Saigo operators are applied to the following special functions: Generalized hypergeometric function, generalization of Hermite’s polynomials and Laguerre’s polynomials.